The Influence of Lecturer Interpersonal Communication on Motivation and Learning Achievement Students of Jinarakkhita Buddhist College - Widiyanto Widi; Rina Manggalani; Wistina Seneru; Resdhi Wibawa; Rini Kasrah (Journal of Communication, Religious, and Social Sciences (JoCRSS), 2023)
The motivation aspect is very important in a learning process in higher education, because motivation determines the intensity of effort in learning and encourages students to carry out certain activities related to the process of gaining knowledge. Learning motivation is one aspect that influences a student's academic achievement. Academic achievement is the result of the learning process as a measure of the quality and quantity of knowledge that students have mastered. Optimal learning outcomes are greatly influenced by various components in teaching and learning, in including lecturer interpersonal communication. This research aims to determine the influence of lecturers' interpersonal communication on students' learning motivation and academic achievement at the Jinarakkhita Buddhist College. This research uses a quantitative approach with correlational methods. Research data is collected using a questionnaire, then the data will be processed and analyzed descriptively. The theoretical basis used is the theory of self-disclosure (Self Disclosure Theory), proposed by Sydney Marshall Jourad. The research results show that interpersonal communication between lecturers and students has an effect on learning motivation by 49.4% with a regression coefficient of 0.469 and a constant of 18.644. Meanwhile, for the academic achievement variable, 32.3% is influenced by lecturer interpersonal communication and the rest is influenced by other factors. Temporary communication lecturer interpersonal influential in a way significant and positive to motivation learning and achievement academic student amounting to 24.4%.